Multicentre evaluation of magnetic technology for localisation of non‐palpable breast lesions and targeted axillary nodes. Issue 11 (17th August 2021) - McCamley, Chere; Ruyssers, Natacha; To, Henry; Tsao, Simon; Keane, Holly; Poliness, Cathie; Mehta, Kirti; Rose, Allison; Baker, Caroline; Mann, Gregory B.
Abstract: Background: Magseed technology is a recently introduced localisation technique for impalpable breast lesions with possible advantages over traditional techniques. These include improved theatre logistics, flexibility in incision placement and improved patient experience. This multicentre study evaluates the experience of introducing Magseed technology into routine surgical practice. Methods: A prospective multicentre study of Magseed localised procedures was performed. Insertion data were recorded by the radiologist including lesion characteristics and Magseed insertion accuracy. The surgical team recorded time from insertion to operation, operating time and surgical satisfaction. Pathology results were reviewed for specimen weight and margins. Results: Between February 2019 and June 2020, 100 patients were enrolled. Magseed localised procedures included 18 excisional biopsies, 23 wide local excisions (WLE), 50 WLE with axillary surgery and four cases of Magseed localised breast WLE with Magseed localised axillary surgery. There were three therapeutic mammoplasties and two cases of Magseed localised targeted axillary node dissection alone. A total of 90% of Magseeds were radiologically placed within 5 mm of the target lesion/node. Time between incision and specimen removal was 17 min (range 6–40 min). All breast and axillary Magseeds were successfully identified and retrieved during surgery. The target lesion was identified in the specimen in all cases. A total of 10% of cases required further surgery for pathologically positive margins. Overall, surgeons reported that Magseed localisation was "easy" or "very easy" in 77% of cases. Conclusion: Magseed is a reliable, safe and accurate surgical technique that provides logistical advantages and flexibility of surgical approach. The method was well‐accepted by all users. Abstract : Magseed localisation of non‐palpable breast lesion. Magseed localisation of non‐palpable breast lesion.